SELECTION OF PARK AND RECREATION AREAS FOR WORKING INDIVIDUALS AND DETERMINATION OF USE RESTRICTIONS - Saraç, Sinan; Kırtepe, Abdurrahman (Nigde Omer Halisdemir University, 2024)
The aim of this research is to examine the park and recreation area selection and usage restrictions of working individuals according to different variables. The relational screening model was used in the research. The study group consisted of a total of 300 working individuals, 217 (r,3) of whom were male and 83 (',7) of whom were female, who volunteered to participate in the study within the borders of the central district of Elazığ province. The study consists of two parts as a data collection tool. The first part was developed by the researchers and consists of 7 items (gender, age, marital status, education status, occupation, place of residence, adequacy of recreation areas in the province). In the second part, the Park-Recreation Area Selection and Usage Restrictors Scale was used. The obtained data were analyzed using the IBM SPSS Statistic 24 statistical package program. In order to determine the tests to be applied to the data, normality (Skewness and Kurtosis) values were first examined. It was determined that the data showed a normal distribution. Independent Sample T-Test was applied for variables with two groups, ANOVA test was applied for variables with more than two groups. Tukey test was used to determine the groups where there was a difference as a result of ANOVA test. As a result, it can be said that gender, marital status, education level, place of residence do not affect individuals' selection of parks and recreation areas and determination of usage restrictions, and according to the age variable; individuals in the 45-54 age group and 65 and over age group are effective in determining parks and recreation areas and usage restrictions compared to individuals between the ages of 35-44.

Bu araştırmanın amacı, çalışan bireylerin park ve rekreasyon alan seçimi ve kullanım kısıtlayıcılarının farklı değişkenlere göre incelenmesidir. Araştırmada ilişkisel tarama modeli kullanılmıştır. Araştırmanın çalışma grubu, Elazığ ili merkez ilçe sınırları içinde çalışmaya gönüllü olarak katılan 217 (%72,3)’si erkek, 83 (%27,7)‘ü kadın, toplam 300 çalışan birey oluşturmuştur. Çalışma da veri toplama aracı iki bölümden oluşmaktadır. Birinci kısım araştırmacılar tarafından oluşturulmuş ve 7 maddeden (cinsiyet, yaş, medeni durum, eğitim durumu, meslek, ikamet yeri, ildeki rekreasyon alanı yeterliliği) oluşmaktadır. İkinci kısımda ise, Park-Rekreasyon Alan Seçimi ve Kullanımı Kısıtlayıcıları Ölçeği kullanılmıştır. Elde edilen veriler IBM SPSS 24 istatistik paket programı kullanılarak analiz edilmiştir. Verilerde uygulanacak testleri belirlemek için öncelikle normallik (Skewness ve Kurtosis) değerlerine bakılmıştır. Verilerin normal dağılım gösterdiği tespit edilmiştir. İkili gruplara sahip değişkenler için Independent Sample T-Testi, ikiden fazla gruba sahip değişkenler için ANOVA testi uygulanmıştır. ANOVA testi sonucunda fark çıkan grupları belirlemek içinse Tukey testi kullanılmıştır. Sonuç olarak cinsiyetin, medeni durumun, eğitim durumunun, ikamet yerinin bireylerin park ve rekreasyon alan seçimi ve kullanım kısıtlayıcılarının belirlenmesini etkilemediği, yaş değişkenine göre ise ; 45-54 yaş grubu ile 65 ve üzeri yaş grubundaki bireylerin, 35-44 yaş arasındaki bireylere göre park ve rekreasyon alan seçimi ve kullanım kısıtlayıcılarının belirlenmesinde etkili olduğu söylenebilir.
ÇALIŞAN BİREYLERİN PARK VE REKREASYON ALAN SEÇİMİ VE KULLANIM KISITLAYICILARININ BELİRLENMESİ
Keywords: Clinical Sciences (Other); Klinik Tıp Bilimleri (Diğer)